PENGARUH INDEKS PEMBANGUNAN MANUSIA (IPM) DAN TINGKAT PENGANGGURAN TERHADAP KEMISKINAN DI KABUPATEN BERAU - Hartono (Prodi Ekonomi Pembangunan, Universitas Muhammadiyah Berau, 2026)
The purpose of this study based on the formulation of the problem is to determine the effect of the Human Development Index (HDI) and unemployment rate partially and simultaneously on poverty in Berau Regency. The secondary data used are time series data of HDI, unemployment, and poverty taken from the Central Statistics Agency (BPS) of Berau Regency for the period 2017-2022. The analytical tools used are: classical assumption test (normality test, autocorrelation test, multicollinearity test, heteroscedasticity test), multiple linear regression analysis, correlation coefficient, determination coefficient, t test, and F test. The conclusions obtained from this study are: 1) The Human Development Index (HDI) has a negative and partially significant effect on the poverty rate in Berau Regency. This is evidenced by the t-count value which is smaller than the minus t-table value (-10.356 < -3.183) with a significance value less than the probability value (0.002 < 0.05); 2) The unemployment rate has a positive and partially significant effect on the poverty rate in Berau Regency. This is based on the t-count value which is greater than the t-table value (9.572 > 3.183) with a significance value smaller than the probability value (0.002 < 0.05); 3) The Human Development Index (HDI) and the unemployment rate have a simultaneous significant effect on poverty in Berau Regency. Proven by the F test where the F-count value is greater than the F-table (60.759 > 9.55) with a significance value smaller than the probability value (0.004 < 0.05).